Peran Yayasan Kalimajari dalam Pemberdayaan Petani Kakao Honey Aromatic Profile melalui Program Kakao Lestari di Desa Pulukan Kecamatan Pekutatan Kabupaten Jembrana - IRHAM MAULANA; I GEDE SETIAWAN ADI PUTRA; I GUSTI AYU AGUNG LIES ANGGRENI (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2021)
The Role Of The Kalimajari Foundation In Empowering Cocoa Farmers In The Honey Aromatic Profile Through a Sustainable Cocoa Program in Pulukan Village, Pekutatan Sub-District, Jembrana Regency Cocoa farmers' high bargaining power and price stability are the desired certainty for farmers. One solution is the empowerment process that is easily accepted by farmers and sustainable. The purpose of empowerment itself is done so that cocoa farmers achieve their welfare. The purpose of this study was to determine the role of the Yayasan Kalimjari and the strategies used in empowering cocoa farmers. The research location is located in Pulukan Village using four informants. The method used in this research is descriptive qualitative. Based on the results of the research the role of empowerment carried out includes human development, business development, institutional development, and environmental development. The strategy used is a mentoring strategy and is cooperative. Empowerment to all assisted farmers are all the same, nothing is distinguished. The results of empowerment can increase farmers' cocoa bargaining power of Rp. 50,000.00 to Rp. 55,000.00 per kg and one of the assisted farmers succeeded in creating an honey aromatic cocoa profile. Although the empowerment carried out succeeded in maintaining and increasing the price of farmers' cocoa, the Yayasan Kalimajari and cocoa farmers must continue to pay attention to the quantity given the current demand is greater than the cocoa beans produced.